2012
DOI: 10.1257/app.4.3.64
|View full text |Cite
|
Sign up to set email alerts
|

Enforcement of Labor Regulation and Informality

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
156
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(173 citation statements)
references
References 32 publications
14
156
1
2
Order By: Relevance
“…Alm et al 1992, Andreoni et al, 1998. Several more recent non-experimental studies in developing countries have found evidence that the degree of enforcement matters for labor informality (Ronconi, 2007;Almeida and Carneiro, 2012), but there is no reliable evidence we are aware of on the impacts of enforcement on firm informality.…”
Section: Introductionmentioning
confidence: 91%
“…Alm et al 1992, Andreoni et al, 1998. Several more recent non-experimental studies in developing countries have found evidence that the degree of enforcement matters for labor informality (Ronconi, 2007;Almeida and Carneiro, 2012), but there is no reliable evidence we are aware of on the impacts of enforcement on firm informality.…”
Section: Introductionmentioning
confidence: 91%
“…This implies the identification of the entire latent wage distribution f 0 (w). Using the latent wage density and the function Λ(w) allows the identification of the latent densities of the formal and informal sectors and, finally, the remaining parameters π (1) m and π…”
Section: Resultsmentioning
confidence: 99%
“…The model allows wages in the informal sector to be affected by the introduction of the minimum wage -an effect captured by the parameter π m . This model also allows workers to move to the informal sector as a response to the minimum wage -this event is captured by the parameter π (1) d . Combined, these unemployment and sector mobility effects allow the minimum wage to affect the relative size of the formal sector in the economy, which in turn can affect labor tax revenues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enforcement, implemented through frequent visits or threats of visits by labor inspectors and the effects on informality and formality are an important, understudied dimension of encouraging formalization. For example, a study in Brazil finds that increases in labor inspections were followed by increases in formal employment and decreases in informal employment [12].…”
Section: Limitations and Gapsmentioning
confidence: 99%